Optimalisasi Administrasi Kurikulum untuk Meningkatkan Mutu Pendidikan di Sekolah Dasar - Yunelda, Diffa; Amelia, Rizki; Novia Sari, Wira (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Curriculum administration is a key element in ensuring the effectiveness and quality of education in elementary schools. This article examines the strategic role of curriculum administration in improving the quality of education through a literature analysis covering planning, implementation, supervision, and evaluation. The role of teachers as implementers, aligners, developers, and researchers is an important aspect in the successful implementation of a curriculum that is adaptive to student needs and local contexts. However, challenges such as limited resources, inconsistencies in policies with local needs, and lack of training for teachers often hinder the effectiveness of curriculum administration. The solutions offered include strengthening school-based management, ongoing training for teachers, community participation, and technology integration in curriculum management. This article concludes that a holistic approach involving cross-sector collaboration and the use of technology can create inclusive, relevant, and quality education. Optimizing curriculum administration is an important foundation for achieving educational goals that are more adaptive and responsive to global and local challenges.